Potential Inter-Fuel Substitution between Hydroelectricity and Fossil Fuels in Nepal - Awasthi, Sudheer; Adhikari, Naveen (Economic Journal of Development Issues, 2019)
In spite of huge hydro-electricity potential, Nepal still relies on fossil fuel to meet its energy demand. However, as the pace of hydroelectricity generation gets momentum in recent years, there are concerns about the excess supply of hydroelectricity in the domestic market in the near future. In this context, this paper examines the potential substitution of conventional fuels by the hydroelectricity in Nepal. Using translog production function, this paper calculates the elasticity of substitution between hydroelectricity, coal, gas, petrol, diesel, and kerosene for the period of 1980 to 2016. Our findings suggest that all the fuels except kerosene are positively associated with economic growth during the study period, and the output elasticity of hydroelectricity is found be largest among these sources of energy. The findings also suggest that hydroelectricity has the potential for substitute other conventional fuels if the share of hydroelectricity is increased in the energy consumption composition. While there is not a huge variation in the elasticity of substitution between hydroelectricity and other fuels, the hydroelectricity has relatively higher potential to substitute coal followed by petrol, diesel, kerosene, and gas. The findings of the paper are supportive of the hypothesis that Nepal could potentially absorb the hydroelectricity generated in near future if incentive mechanisms are initiated that allow substitution of conventional fossil fuels by the hydroelectricity.